2021
DOI: 10.1186/s42862-021-00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immediate impact of Faculty Development Programme using a pretest–post-test study design format

Abstract: Background Workshops are the most common models to enhance knowledge and skills in a specific subject area with an intent to explore, solve a problem and/or innovate new things. The most important aspect of a workshop is the transfer of knowledge in a safe learning environment as a faculty development activity (FDA). At International Medical University (IMU), Malaysia’s first private medical university which was established in 1992, Faculty Development Programmes (FDPs) are run throughout the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Hassan et al. (2021a, b) noted a significant improvement in the faculty knowledge indicating an immediate positive impact of FDPs. A four-year-long empirical study (Quirk et al.…”
Section: Review Of Literaturementioning
confidence: 88%
See 1 more Smart Citation
“…Hassan et al. (2021a, b) noted a significant improvement in the faculty knowledge indicating an immediate positive impact of FDPs. A four-year-long empirical study (Quirk et al.…”
Section: Review Of Literaturementioning
confidence: 88%
“…Similarly, Hassan et al. (2021a, b) underlined the critical nature of FDPs in enhancing knowledge, skills, and overall quality of education.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the early years, moreover, many studies proved the efficiency of Faculty Development initiatives to promote teachers' professional development and support in their teaching academic career (Hassan et al, 2021). Especially in the medical education, indeed, we have evidences of the relevant impact of Faculty Development programs in changing faculty's behaviour in terms of teaching and learning, thanks to case studies (Stake, 1995) which analyzed, through questionnaires and pre/post tests, the changes in teachers' willingness and awareness on their educational role (Lee et al, 2018).…”
Section: • Teaching Support Provided By Specialists • Teaching Qualit...mentioning
confidence: 99%
“…These include interest in the participants, previous training sessions attended, exposure to reading material, level of seriousness, and renewed interest in the concept being elaborated. A study conducted on the impact of workshops on topics pertaining to medical education technologies concluded that knowledge levels increased immediately after attendance, decreasing at two months, and then reverting at six months [ 21 ]. This variation in the ability of participants to recall and utilize the information given to them through FDTW can be used to determine the frequency at which FDTW should be organized.…”
Section: Introductionmentioning
confidence: 99%